Comprehensive analysis of the mechanisms conferring resistance to phenamacril in the Fusarium species - Alexander Dumbai Joe; Runze Liu; Xiao Luo; Ruqiya Syed; Farhan Aslam; Zhenying Luo; Zhitian Zheng (Frontiers in Cellular and Infection Microbiology)
The filamentous fungal genus Fusarium contains many species that cause catastrophic diseases in fruits, cereal, and vegetables. These diseases cause substantial losses in yield and contaminate affected crops with toxins. This causes huge losses in the agricultural sector and threatens human and animal health. The most efficient approach to control the Fusarium spp. is fungicide application. Phenamacril is a site-specific fungicide that exerts its antifungal effect on sensitive Fusarium spp. It is a new fungicide developed that targets Fusarium graminearum by inhibiting myosin-5, an important protein in fungal growth and disease development. Because of its remarkable specificity, the new fungicide phenamacril is regarded as environmentally benign. However, many research findings have reported the emergence of the resistance of Fusarium spp. to phenamacril in both the field and laboratory. This article comprehensively analyzes the mechanisms underlying Fusarium spp. resistance to phenamacril. We examine the molecular, genetic, and environmental factors contributing to this resistance. We emphasize the importance of continued research and integrating different approaches to monitoring and managing drug-resistant Fusarium spp. populations. Integrating current inventions to inform strategies for sustainable disease control practices, and increase plant health, and yield will contribute to ongoing global efforts to achieve food and nutritional sustainability for the world's rapidly growing population while ensuring the effectiveness of the fungicidal product.